Analysis of the daily changes of melatonin receptors in the rat liver. Issue 3 (30th October 2012) - Venegas, Carmen; García, José A.; Doerrier, Carolina; Volt, Huayqui; Escames, Germaine; López, Luis C.; Reiter, Russel J.; Acuña‐Castroviejo, Darío
Abstract Melatonin membrane (MT1 and MT2) and nuclear (RORα) receptors have been identified in several mammalian tissues, including the liver. The mechanisms regulating hepatic melatonin receptors are yet unknown. This study investigated whether these receptors exhibit daily changes and the effects of melatonin on their levels. Our results show that mRNAs for MT1/MT2 receptors exhibit circadian rhythms that were followed by rhythms in their respective protein levels; the acrophases for the two rhythms were reached at 04:00 and 05:00 hr, respectively. Pinealectomy blunted the rhythms in both mRNAs and protein levels. In contrast, mRNA and protein levels of nuclear receptor RORα increased significantly after pinealectomy. The cycles of the latter receptor also exhibited circadian rhythms which peaked at 03:00 and 03:45 hr, respectively. Melatonin administration (10–200 mg/kg) increased in a dose‐dependent manner the protein content of MT1/MT2 receptors, with no effects on RORα. Lunzindole treatment, however, did not affect melatonin receptor expression or content of either the membrane or nuclear receptors. Together with previously published findings which demonstrated the intracellular distribution of melatonin in rat liver, the current results support the conclusion that the circadian rhythms of MT1/MT2 and RORα receptors are under the control of the serum and intracellular melatonin levels. Moreover, the induction of MT1/MT2 receptors after the administration of high doses of melatonin further suggests that the therapeutic value of melatonin may not be restricted to only low doses of the indoleamine.